2010
DOI: 10.1111/j.1447-0349.2010.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of resilience and job satisfaction among psychiatric nurses working in inpatient units

Abstract: The present exploratory study was designed to examine the relationship between resilience and job satisfaction in psychiatric nurses working in inpatient units in a large, urban medical centre. The long range goal was to understand the dimensions of job satisfaction in this inpatient environment in order to implement nurse retention programmes specifically targeted toward teaching nurses skills in developing resilience. The nurses (n = 32) reported a high level of resilience and high job satisfaction. The job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 30 publications
8
106
0
11
Order By: Relevance
“…El tamaño de la muestra se estableció a partir de la relación entre resiliencia y satisfacción laboral reportada por Matos et al (2010) de r=0,33. Considerando como estimada una correlación poblacional de ρ=0,3, para obtener un poder de 0,8 con un nivel de significación de 0,05 se necesitaba una muestra de mínimo 85 personas.…”
Section: Participantesunclassified
“…El tamaño de la muestra se estableció a partir de la relación entre resiliencia y satisfacción laboral reportada por Matos et al (2010) de r=0,33. Considerando como estimada una correlación poblacional de ρ=0,3, para obtener un poder de 0,8 con un nivel de significación de 0,05 se necesitaba una muestra de mínimo 85 personas.…”
Section: Participantesunclassified
“…Resilient organizations are able to create work environments that contribute to organizational productivity, and improve the psychological and physical health of their workers (Harland, Harrison, Jones, & Reiter-Palmon, 2005;Laschinger, 2010). Specifically in the setting we are dealing with here, a healthy and resilient healthcare organization would be one that strives to ensure the quality of the working life of its employees, as well as to survive and thrive in the context of economic and social change; in other words we are talking about those which are able to create work environments that can help improve the practice and health of healthcare professionals, and enhance the service quality provided to the patient/family (Matos, Neushotz, Griffin, & Fitzpatrick, 2010;McAllister & Lowe, 2011;Salanova, Rodríguez-Sánchez, Del Líbano, & Ventura, 2012). Broadly speaking, Salanova (2008) defined HEROs as organizations that make systematic, planned, and proactive efforts to improve the health of their employees and the organization itself through healthy organizational practices that relate to the improvement of job characteristics at three levels: (1) task level (e.g., task redesign to improve autonomy, feedback); (2) social environment level (e.g., leadership); and (3) organizational level (e.g., organizational strategies for improving health, and work-family balance).…”
Section: Theoretical Model: the Hero Modelmentioning
confidence: 99%
“…In one of the few studies on resilience and job strains, researchers sought to examine the relationship between resilience and job satisfaction in nurses, and found that over 10% of the variance in job satisfaction could be explained by resilience (Matos et al, 2010). Despite research on the relationship between resilience and its antecedents and outcomes in health care workers, no research has examined the role of resilience in the stressor-strain process.…”
Section: Hypothesis 11 (H11): Resilience Will Be Negatively Correlatementioning
confidence: 99%
“…The goal of such resilience interventions for nurses is to improve important outcomes such as turnover intentions (Elitharp, 2006;Hoopes, 2012), burnout, and job satisfaction (Elitharp, 2006, Matos, Neushotz, Griffin, & Fitzpatrick, 2010. Given that outcomes such as turnover can harm an organization's ability to provide quality care and meet patient needs (Tai, Bame, & Robinson, 1998), promoting resilience in the workplace could provide positive outcomes for organizations as well as nurses.…”
Section: Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation